C-Met-targeted near-infrared fluorescent probe for real-time depiction and dissection of perineural invasion and lymph node metastasis lesions in pancreatic ductal adenocarcinoma xenograft models. (13th July 2021) - Li, Dan; Yang, Meilin; Liang, Mingzhu; Mei, Chaoming; Lin, Yujing; Yang, Fan; Xiao, Yitai; Chen, Yuechuan; Wang, Fen; Mao, Junjie; Su, Zhongzhen
Abstract : c-Met-targeted near-infrared fluorescent probe has excellent targeting ability to pancreatic ductal adenocarcinoma (PDAC), and can be used for real-time detection of lymph node metastasis and perineural invasion lesions in PDAC xenograft models. Abstract : Pancreatic ductal adenocarcinoma (PDAC), a fatal malignant tumour, has a high postoperative recurrence rate, mainly due to the difficulty of discerning occult lesions, including those related to perineural invasion (PNI) and lymph node metastasis (LNM). Cellular mesenchymal-epithelial transition factor (c-Met), an excellent imaging marker, is aberrantly expressed in the majority of PDACs. Thus, we plan to utilize a c-Met-targeted near-infrared fluorescent (NIRF) probe for real-time visualization and dissection of PDAC, and corresponding PNI and LNM lesions. Immunohistochemistry showed c-Met expression in PDAC, PNI and LNM reached 94.3% (100/106), 88.3% (53/60), and 71.4% (25/35), respectively, and its expression in PNI and LNM was significantly correlated with that in primary PDAC ( r = 0.66, p < 0.0001 and r = 0.44, p < 0.01, respectively). SHRmAb-IR800 was successfully synthesized using an anti-c-Met antibody and a NIRF dye. The in vitro targeting ability of SHRmAb-IR800 was higher in CFPAC1 cells (c-Met positive) than in Miapaca-2 cells (c-Met negative) ( p < 0.05). In vivo NIRF imaging of CFPAC1 subcutaneous tumours demonstrated higher accumulation of SHRmAb-IR800 than the control probe ( p < 0.05). The signal-to-background ratio (TBR) of an orthotopic PDAC tumour was 3.38 ± 0.46, and imaging with SHRmAb-IR800 facilitated the resection of metastatic lesions with sensitivity and specificity values of 93.3% (56/60) and 87.1% (27/31), respectively. Furthermore, tiny PNI and LNM lesions in xenograft models were detected by NIRF imaging, with TBRs measuring 2.59 ± 0.19 and 2.88 ± 0.72, respectively. Therefore, the clinical translation of this probe might shed new light on NIRF-guided pancreatectomy and improve the surgical prognosis of PDAC patients.